Inhibition of endothelial nitric oxyde synthase increases capillary formation via Rac1-dependent induction of hypoxia-inducible factor-1α and plasminogen activator inhibitor-1 - Petry, Andreas; BelAiba, Rachida S.; Weitnauer, Michael; Görlach, Agnes (Thrombosis and Haemostasis, 2012)
Disruption of endothelial homeostasis results in endothelial dysfunction, characterised by a dysbalance between nitric oxide (NO) and reactive oxygen species (ROS) levels often accompanied by a prothrombotic and proproliferative state. The serine protease thrombin not only is instrumental in formation of the fibrin clot, but also exerts direct effects on the vessel wall by activating proliferative and angiogenic responses. In endothelial cells, thrombin can induce NO as well as ROS levels. However, the relative contribution of these reactive species to the angiogenic response towards thrombin is not completely clear. Since plasminogen activator inhibitor-1 (PAI-1), a direct target of the proangiogenic transcription factors hypoxia-inducible factors (HIFs), exerts prothrombotic and proangiogenic activities we investigated the role of ROS and NO in the regulation of HIF-1α, PAI-1 and capillary formation in response to thrombin. Thrombin enhanced the formation of NO as well as ROS generation involving the GTPase Rac1 in endothelial cells. Rac1-dependent ROS formation promoted induction of HIF-1α, PAI-1 and capillary formation by thrombin, while NO reduced ROS bioavailability and subsequently limited induction of HIF-1α, PAI-1 and the angiogenic response. Importantly, thrombin activation of Rac1 was diminished by NO, but enhanced by ROS. Thus, our findings show that capillary formation induced by thrombin via Rac1-dependent activation of HIF-1 and PAI-1 is limited by the concomitant release of NO which reduced ROS bioavailability. Rac1 activity is sensitive to ROS and NO, thereby playing an essential role in fine tuning the endothelial response to thrombin.
Keywords: Thrombin; angiogenesis; nitric oxide; reactive oxygen species; PAI-1